Decline in Pneumococcal Nasopharyngeal Carriage of Vaccine Serotypes After the Introduction of the 13-Valent Pneumococcal Conjugate Vaccine in Children in Atlanta, Georgia. Issue 11 (November 2015) - Desai, Ankita P.; Sharma, Dolly; Crispell, Emily K.; Baughman, Wendy; Thomas, Stepy; Tunali, Amy; Sherwood, Logan; Zmitrovich, April; Jerris, Robert; Satola, Sarah W.; Beall, Bernard; Moore, Matthew R.; et al.
Abstract : Background: Streptococcus pneumoniae (SP) serotype distribution among nasopharyngeal (NP) carriage isolates changed significantly after the introduction of the 7-valent pneumococcal conjugate vaccine (PCV7). We evaluated the impact on NP carriage and invasive disease of SP after the introduction of the 13-valent PCV (PCV13) in March 2010. Methods: NP swabs were collected from children 6–59 months of age in an emergency department from July 2010 to June 2013. After broth enrichment, samples were cultured for SP and isolates were serotyped. Clinical and immunization records were reviewed. Findings during 6 sequential 6-month study periods were compared. Surveillance isolates of invasive disease isolates were reviewed. Results: A total of 2048 children were enrolled, and 656 (32%) were SP carriers. Mean age of carriers was 27 months, 54% were males. Carriage was higher among day-care attendees ( P < 0.01) and children with respiratory tract illnesses ( P < 0.5) and otitis media ( P < 0.01). Commonly carried serotypes included 35B (15.2%), 15B/C (14.2%), 19A (9.6%), 11A (8%), 23B (5.6%), 6C (5.3%), 21 (5%), and 15A (5%); 13.9% were PCV13 serotypes. The proportion of children with SP carriage remained stable but the serotype distribution changed during the study period. Among carriers, PCV13 serotypes declined from 29% (36/124) to 3% (3/99; P < 0.0001), predominantly because of decline of serotype 19A from 25.8% (32/124) to 3% (3/99; P < 0.0001); non-PCV13 serotypes (excluding 6C) increased from 68.4% (78/114) to 97% (95/98; P < 0.0001); serotype 35B significantly increased from 8.9% (11/124) to 25.3% (25/99; P < 0.05). Nonsusceptibility to ceftriaxone declined from 22.6% (28/124) to 0% (0/99; P < 0.0001), with a similar decline in penicillin nonsusceptibility. Conclusions: Introduction of PCV13 for universal infant use was associated with significant reductions in nasopharyngeal carriage of PCV13 serotypes and resistant strains. Carriage of non-PCV13 serotypes increased modestly, particularly serotype 35B. Further investigation is warranted to determine whether nonvaccine pneumococcal serotypes carried in the nasopharynx are associated with significant replacement disease. Abstract : Supplemental Digital Content is available in the text.